2015
DOI: 10.5539/ies.v8n11p219
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Organizational Trust and Organizational Silence with Job Satisfaction and Organizational Commitment of the Employees of University

Abstract: This study aimed to investigate the structural model between organizational trust and organizational silence with job satisfaction and organizational commitment of the employees of Islamic Azad University of Isfahan, (Khorasgan) branch. The study method is descriptive-correlation. The study population is the employees of Islamic Azad University of Isfahan branch (Khorasgan) as 340. 180 employees are selected by simple random method and sampling Table (Krejcie & Morgan, 1970). The questionnaires of organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 13 publications
4
56
0
11
Order By: Relevance
“…The results of studies showed that interpersonal trust in employees and creating trustful climate led into high level of commitment and performance improvement. Fard and Fariba [14] indicated that, organizational trust had direct impact on organizational silence, organizational commitment and job satisfaction and had indirect impact via organizational silence on organizational commitment and job satisfaction. Also, organizational silence had direct impact on organizational commitment and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies showed that interpersonal trust in employees and creating trustful climate led into high level of commitment and performance improvement. Fard and Fariba [14] indicated that, organizational trust had direct impact on organizational silence, organizational commitment and job satisfaction and had indirect impact via organizational silence on organizational commitment and job satisfaction. Also, organizational silence had direct impact on organizational commitment and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in the organization, in turn, is the relationship between the organization and employees, which is built mainly on employees’ organizational expectations and supervisor perceptions (Fard and Karimi ). Employees who trust their organizations are likely to be satisfied with their jobs, exhibit better performance, adopt organizational values, and display citizenship behaviors (Galford and Drapeau ).…”
Section: Transformational Leadership and Job Satisfactionmentioning
confidence: 99%
“…He also said organizational cynicism and organizational mistrust had unfavorable effect on workers' performance. Besides, Fard and Karimi (2015), Ajayi et al (2011), andTekingündüz, Top, Tengilimoğlu, andKarabulut (2015) underlined that organizational trust contribute to jobsatisfaction and job performance. On the other hand, there are some other studies which claim that social safeness and pleasure are positively associated with life satisfaction, meaning of the life, life quality, flourishing, authentic living and extraversion (Satici, Uysal, & Akin, 2013;Uysal, 2015aUysal, , 2015b.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%